2017
DOI: 10.3171/2016.6.jns16154
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for bionic hand reconstruction in patients with global brachial plexopathies

Abstract: OBJECTIVE Global brachial plexus lesions with multiple root avulsions are among the most severe nerve injuries, leading to lifelong disability. Fortunately, in most cases primary and secondary reconstructions provide a stable shoulder and restore sufficient arm function. Restoration of biological hand function, however, remains a reconstructive goal that is difficult to reach. The recently introduced concept of bionic reconstruction overcomes biological limitations of classic reconstructive surgery to restore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 40 publications
0
37
0
4
Order By: Relevance
“…Global upper extremity function using two objective functional tests was assessed at three time points: before bionic reconstruction using the functionless arm; shortly before amputation using a hybrid prosthetic arm [15,16] mounted on the functionless arm of the patient; and after successful prosthetic reconstruction.…”
Section: Functional Outcome Measuresmentioning
confidence: 99%
See 4 more Smart Citations
“…Global upper extremity function using two objective functional tests was assessed at three time points: before bionic reconstruction using the functionless arm; shortly before amputation using a hybrid prosthetic arm [15,16] mounted on the functionless arm of the patient; and after successful prosthetic reconstruction.…”
Section: Functional Outcome Measuresmentioning
confidence: 99%
“…Following complex brachial plexus injuries, nerve regeneration often leads to partial re-innervation of muscles in the affected arm. Although without clinical significance to the patient, faint muscle activity may therefore still be detectable with transcutaneous electromyographic (EMG) sensors [15]. Recently, it has been shown that this residual myoactivity suffices to translate into dexterous prosthetic hand control after elective amputation and prosthetic replacement of the functionless plexus hand, a concept today known as bionic reconstruction [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations